Method for enriching precious metal from nickel anode slime desulfurization tailings - SONG HONGRU; ZHANG NAIYU; WANG JUN; ZHOU JUNHUA; WANG YANQIANG; ZUO FUMIN; ZHANG YAN; AN GUORUI; ZHANG XIAOKAI; LIU SHENGWEI; ZHOU HELI (2025)
The invention belongs to the technical field of precious metal hydrometallurgy, and particularly relates to a method for enriching precious metal from nickel anode slime desulfurized tailings, which comprises the following steps: combining sodium sulfite with elemental sulfur in the nickel anode slime desulfurized tailings to realize 98% removal of elemental sulfur in the nickel anode slime desulfurized tailings; meanwhile, a high-quality sodium thiosulfate product can be obtained, and the goal of zero discharge of alkaline wastewater is achieved. By means of the method, the direct recovery rate of gold, platinum and palladium precious metal (namely, the mass content of the precious metal in the finally obtained concentrate accounts for the mass content of the precious metal in the nickel anode mud desulfurization tailings) is larger than 99%, the grade of the finally obtained concentrate is high, the content of gold, platinum and palladium reaches up to 10-15%, and the concentrate can directly enter the extr